Postcommunism - Sakwa, Richard. (Open University Press, 1999)
This book is divided into seven parts: Introduction: Defining Postcommunism; The Long Transcendence; The Communist Experience; Postcommunism in Practice; Coming to terms with Communism; Paradoxes and Paradigms; and Postcommunism in Perspective.